2009
DOI: 10.1017/s0959259809990190
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry of old age and ethnic minority older people in the United Kingdom

Abstract: SummaryThis review examines the demographic changes, the epidemiology of mental disorders and suicides, the potential risk and protective factors, access to secondary care old age psychiatry services (OAPSs) and the policy context pertaining to older people from ethnic minority groups in the United Kingdom. The number of older people from ethnic minority groups is increasing. The prevalence of mental disorders in older people from ethnic minority groups is either similar to or higher than that in the indigenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Similarly, a Norwegian study reported that mental health problems among older immigrants are due to the accumulation of stressors resulting from a paucity of culturally appropriate resources to meet daily needs (Gele & Harsløf, 2012). The high comorbidity between mental health problems and neurological problems in old age is also worth considering (Shah, 2009). The emergence of somatic illnesses can weaken psychological well-being especially among older adults, and their acculturation process is slower than that of young refugees and immigrants.…”
Section: Older Somali Refugeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a Norwegian study reported that mental health problems among older immigrants are due to the accumulation of stressors resulting from a paucity of culturally appropriate resources to meet daily needs (Gele & Harsløf, 2012). The high comorbidity between mental health problems and neurological problems in old age is also worth considering (Shah, 2009). The emergence of somatic illnesses can weaken psychological well-being especially among older adults, and their acculturation process is slower than that of young refugees and immigrants.…”
Section: Older Somali Refugeesmentioning
confidence: 99%
“…The health care system ignores their holistic experiences of social suffering and culturally-bound symptom manifestation, and often fails to listen to spiritual, historic, and culturally unique illness explanations that could serve as a basis for healing and provide a sense of security (Groleau & Kirmayer, 2004;Mo¨lsa¨, Hjelde, & Tiilikainen, 2010). Previous research confirms that mental health services lack culturally insightful healing practices for refugees, for example, in the UK (McColl & Johnson, 2006;Shah, 2009) and the Netherlands (Gerritsen et al, 2006b). A US study found that due to institutional barriers, even mentally ill older immigrants can receive less care than the healthy native population (Jackson et al, 2007).…”
Section: Older Somali Refugeesmentioning
confidence: 99%
“…The high frequency of occurrence and severity of mental disorders are strongly correlated with individuals' socio-economic circumstances, including factors such as poverty, income inequality, or involuntary migration [5,6]. The social determinants of mental health that stand out the most in the literature are demographic, which include gender, age, ethnicity, and life expectancy [7][8][9][10][11]; economic, where financial and employment status, housing, and income inequality are considered [12][13][14][15]; an individual's area of residence, which is related to variables such as safety, the availability of services, and places of recreation [16][17][18][19]; environmental events, such as natural disasters and armed conflicts, as well as hazards to the ecosystem due to climate change [20][21][22]; and the sociocultural domain, which encompasses education, interpersonal relationships, social capital, culture, and a person's sense of belonging in their community [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic minority group has been identified in several studies as a moderator for the prevalence rate of dating violence victimization and perpetration. Ethnic minority status refers to youth who report a different racial or cultural group from the majority population where they reside [ 15 ]. According to Capaldi et al ’s review article [ 4 ], victimization and perpetration rates are higher among African American youth, although these differences diminish after controlling for reduced socio-economic status and income.…”
Section: Introductionmentioning
confidence: 99%